Growth and Characterization of Doped ADP Crystal - M. Mary Freeda1, R. Krishna Priya2, Abdul Wahab Almusallam3, T. Ananthi1, S. Mary Delphine1* (Recent Research in Science and Technology, 2010)
Pure and impurity added (urea) Ammonium dihydrogen orthophosphate (ADP) single crystals were grown by the slow evaporation technique.Â Crystallinity of the pure and doped crystal has been studied by XRD analysis. Fourier transform infrared (FTIR) studies confirm the functional group of the crystals. Thermal studies (TG/DTA) confirm that decomposition temperatures of the doped crystals have been decreased.Â Â